Integrated urban water resources management strategy for a smart city in India - S. Chandran (IWA Publishing, 2021)
Economic growth of any nation like India depends on growth of cities. In India 31% of the total population exists in urban areas. The smart city mission of India was established with the objective to deliver the basic requirements of the citizens in a sustainable manner. Madurai city located at Peninsular India with a 1.4 million population was taken for this study. The objective was to develop an integrated urban water management strategy after analysing all the components of the urban water cycle such as rainfall, runoff, groundwater and wastewater. The population forecast for 2021 was carried out for the Local Planning Area of 726.34 km2 and the water demand was calculated as 109 Mm3/year. To meet the demand, runoff from the average rainfall was estimated as 393 Mm3/yr using the SCS-CN method. The storage capacity in the water bodies to store the surface water was estimated as 156 Mm3/yr and groundwater recharge potential was estimated as 22 Mm3/yr. The integrated urban water management strategy developed, shows that there is a huge potential for rainwater storage at the surface level and subsequent recharge through artificial recharge techniques. HIGHLIGHTS An overview of an integrated urban water management strategy is projected for a smart city in India.; The status of water demand and existing status of water resources is discussed.; Need for groundwater recharge is debated.; Abundance existence of wastewater and its potential to manage water demand is proposed.; The study tries to state that water demand is more management than scarcity and stress.;